Does Carbon Emissions, and Economic Expansion Induce Health Expenditure in China: Evidence for Sustainability Perspective - Xiu, Juhua; Salem, Sultan; Adebayo, Tomiwa S.; Altuntaş, Mehmet (Frontiers in Environmental Science, 2022)
The current paper assesses the drivers of health care expenditure such as urbanization, natural resources, economic expansion, and CO2 utilizing quarterly data from 2000Q1 to 2018Q4. The research applied the novel dual adjustment approach to identify the long run association between healthcare expenditure and urbanization, economic growth, natural resource and CO2 emissions. The dual adjustment approach’s main novelty is that it gives an option for cointegration analysis by decreasing the implicit assumption of single adjustment. The outcome of the dual adjustment approach affirmed cointegration among the variables in the long run. Furthermore, we applied FMOLS, DOLS and CCR estimators and their findings disclosed that economic growth, urbanization, and CO2 emissions increase health care expenditure while natural resource rent mitigates healthcare expenditure in China. Moreover, the spectral causality test uncovered that urbanization, economic growth, natural resource, and CO2 can predict healthcare expenditure at various frequencies. Based on these findings, China's policymakers should establish strategic environmental management policies that improve healthy and clean air to reduce healthcare costs. In addition, policymakers in China should reevaluate their urban development strategies to avoid negative externalities associated with fast urbanization